Study of operational characteristics and structural-phase state Fe-Ni-Co the invar - Тусупжaнов, А.Е.; Мурaтбеков, Б.М.; Кaнтaй, Н. (Recent Contributions to Physics, 2016)
Materials on the base of multifunctional alloys with the special physical and mechanical properties for developing the equipment of new generation are in high demand at present. Among these materials are Invar alloys with the minimum thermal expansion and the increased level of mechanical properties, in particular, strength and hardness. The work carried out smelting of Invar alloy Fe-Ni-Co with the addition of alloying elements, the microhardness of the resulting alloy is Нμ = 6433 MPa. It is found that after the annealing at temperature for one hour 8000С alloy microhardness increased by 15%. As a result of X-ray diffraction studies showed that the alloy in the initial state consists of a FeNi-phase with a face-centered cubic lattice and α-Fe with a volume-centered cubic lattice. Microstructural studies have shown that in the initial state, the alloy has an acicular structure with needle phases width of about 2 mm, since the acicular particles annealing markedly broadened.